Excessive daytime sleepiness among children and adolescents: prevalence, correlates, and pubertal effects - Liu, Yaping; Zhang, Jihui; Li, Shirley Xin; Chan, Ngan Yin; Yu, Mandy Wai Man; Lam, Siu Ping; Chan, Joey Wing Yan; Li, Albert Martin; Wing, Yun Kwok (Sleep medicine, 2019)
To examine the prevalence and correlates of excessive daytime sleepiness (EDS) among Hong Kong children and adolescents. We investigated the potential roles of sex and puberty in modulating the occurrence of EDS. A total of 10,086 students (male, 48.1%) aged 6–18 (mean ± SD: 12.3 ± 3.2) years old participated in this cross-sectional survey. EDS was defined by a total score >18 on the Pediatric Daytime Sleepiness Scale. Sociodemographic characteristics, time in bed, chronotypes, sleep problems, emotional and behavioral difficulties, mental health, and pubertal stages were assessed. The overall prevalence of EDS was 29.2%, and increased from 19.8% at Tanner stage 1 (pre-puberty) to 47.2% at Tanner stage 5 (post-puberty). Female predominance emerged at Tanner stage 3 (mid-puberty). EDS was significantly associated with short weekday time in bed, both long and short weekend time in bed, eveningness chronotype, insomnia symptoms, and sleep-disordered breathing symptoms. Females were more likely to have short weekday time in bed and eveningness chronotype than males. Children and young adolescents at pre and mid-puberty were protected against EDS by morningness chronotype. EDS was independently associated with daytime napping, alcohol and energy beverage consumption, emotional and behavioral difficulties, as well as poor mental health even after adjusting for potential confounding factors. EDS is prevalent among children and adolescents with the emergence of female preponderance at mid-puberty and independent association with pervasive adverse emotional and behavioral problems. The mechanisms underlying the modulation effects of sex and puberty on EDS merit further investigation. •Excessive daytime sleepiness is prevalent among children and adolescents.•The prevalence of sleepiness dramatically increases with age and pubertal maturation.•Female-predominance of sleepiness emerges after mid-puberty.•Puberty and sex moderate sleepiness through interaction with time in bed and chronotype.•Sleepiness is independently associated with an array of mental and behavioral problems.